Association of anticardiolipin, antiphosphatidylserine, anti-β2 glycoprotein I, and antiphosphatidylcholine autoantibodies with canine immune thrombocytopenia. Issue 1 (December 2016) - Chen, Yu-Chen; Chi, Lang-Ming; Chow, Kuan-Chih; Chiou, Shiow-Her; Fan, Yi-Hsin; Ho, Shu-Peng; Hsu, Yu-Chen; Hwang, Yu-Chyi; Wu, Meng-Xing; Lee, Wei-Ming; Lin, Shiun-Long; Tsang, Chau-Loong; et al.
Abstract Background In humans, the presence of antiphospholipid antibodies (aPL) is frequently found in immune thrombocytopenia. The present study investigated whether aPL and any aPL subtypes are associated with canine thrombocytopenia, in particular, immune-mediated thrombocytopenia (immune thrombocytopenia) that usually manifests with severe thrombocytopenia. Results Sera were collected from 64 outpatient dogs with thrombocytopenia (Group I, platelet count 0 – 80 × 103 /uL), and 38 of which having severe thrombocytopenia (platelet count < 30 × 103 /uL) were further divided into subgroups based on the presence of positive antiplatelet antibodies (aPLT) (subgroup IA, immune thrombocytopenia, n =20) or the absence of aPLT (subgroup IB, severe thrombocytopenia negative for aPLT, n =18). In addition, sera of 30 outpatient dogs without thrombocytopenia (Group II), and 80 healthy dogs (Group III) were analyzed for comparison. Indirect ELISAs were performed to compare serum levels of aPL subtypes, including anticardiolipin antibodies (aCL), antiphosphatidylserine antibodies (aPS), antiphosphatidylcholine (aPC), and anti-β2 glycoprotein I antibodies (aβ2 GPI), and antiphosphatidylinositol antibodies (aPI), among different groups or subgroups of dogs. Among outpatient dogs, aCL, being highly prevalent in outpatient dogs with thrombocytopenia (63/64, 98 %), is an important risk factor for thrombocytopenia (with a high relative risk of 8.3), immune thrombocytopenia (relative risk 5.3), or severe thrombocytopenia negative for aPLT (relative risk ∞, odds ratio 19). In addition, aPS is a risk factor for immune thrombocytopenia or severe thrombocytopenia negative for aPLT (moderate relative risks around 2), whereas aPC and aβ2 GPI are risk factors for immune thrombocytopenia (relative risks around 2). Conclusions Of all the aPL subtypes tested here, aCL is highly associated with canine thrombocytopenia, including immune thrombocytopenia, severe thrombocytopenia negative for aPLT, and less severe thrombocytopenia. Furthermore, aPS is moderately associated with both canine immune thrombocytopenia and severe thrombocytopenia negative for aPLT, whereas aβ2 GPI, and aPC are moderately relevant to canine immune thrombocytopenia. In contrast, aPI is not significantly associated with canine immune thrombocytopenia.